Exploitation of a tristable nonlinear oscillator for improving broadband vibration energy harvesting. Issue 3 (20th August 2014) - Zhou, Shengxi; Cao, Junyi; Lin, Jing; Wang, Zezhou
Abstract : Numerical and experimental investigations of a broadband vibration energy harvester with triple-well are presented. The nonlinear restoring force of the tristable oscillator is experimentally identified as a high order polynomial that depends on the relative spacing and locations of the magnets in the magnetically coupled piezoelectric cantilever. Simulations and experiments are performed at different harmonic excitation levels ranging from 10 to 35 Hz. The tristable energy harvester possesses the unique jump characteristics of oscillation center stemming from excitation level and initial displacements. Its broad frequency range of 15.1–32.5 Hz is obtained from the transition among three wells. It is also demonstrated that the tristable nonlinear oscillator will be more helpful to improve the broadband performance for harvesting vibration energy under low frequency excitations.